Silicon-silicon complex oxide-carbon composite material, its preparation method, and negative electrode active material containing the same
Patent Information
- Application Number
- JP2022544356
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-21
- Filing Date
- 2021-01-19
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2041-01-19
AI Technical Summary
【0020】 本実施形態のケイ素-ケイ素コンプレックス酸化物-炭素複合材料は、コア-シェル構造を有し、該コアがケイ素、酸化ケイ素化合物、およびケイ酸マグネシウムを含み、該シェルが炭素層を含み、前記複合材料の粒子寸法分布が、特定の範囲において式1のスパン値を満たすよう調整される。そのため、二次電池の負極活物質として使用した場合、容量だけでなく、二次電池のサイクル特性および初期効率も高めることができる。
Smart Images

Figure 0007636006000008 
Figure 0007636006000001 
Figure 0007636006000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a silicon-silicon complex oxide-carbon composite material, a method for preparing the same, and a negative electrode active material for a lithium secondary battery containing the same. [Background technology]
[0002] In recent years, with the development of the information and communications industry, electronic devices have become smaller, lighter, thinner, and more portable, and this has led to an increased demand for batteries with high energy density to be used as the power source for these electronic devices. Lithium secondary batteries are the batteries that can best meet this demand, and research into small batteries using these batteries, as well as their application to large electronic devices such as automobiles and power storage systems, is being actively conducted.
[0003] Carbon materials are widely used as the negative electrode active material in such lithium secondary batteries. To further improve the capacity of the battery, silicon-based negative electrode active materials are being researched. The theoretical capacity of silicon (4,199 mAh / g) is more than 10 times that of graphite (372 mAh / g), so a significant improvement in battery capacity is expected.
[0004] However, when silicon is used as the main raw material for the negative electrode active material, the negative electrode active material may expand or contract during charging and discharging, and cracks may form on the surface or inside of the negative electrode active material. As a result, the reaction area of the negative electrode active material increases, a decomposition reaction of the electrolyte occurs, and a film is formed by the decomposition product of the electrolyte during the decomposition reaction, which may cause a problem of reduced cycle characteristics when used in a secondary battery. Therefore, attempts to solve this problem have been made.
[0005] Specifically, Patent Document 1 discloses an anode active material including a carbon layer formed on the surface of silicon oxide particles in order to realize high capacity and safety of secondary batteries. However, although the anode active material can increase the charge / discharge capacity and energy density of secondary batteries, the cycle characteristics may be insufficient, or it may be difficult to obtain an energy density that meets market needs.
[0006] Patent Document 2 discloses a method for preparing a silicon-silica composite material containing magnesium or calcium by reacting silicon dioxide powder coated with carbon with magnesium hydride (MgH2) or calcium hydride (CaH2) in order to suppress the irreversible reaction of silicon dioxide. In this method, the amount of oxygen decreases during the reaction between silicon dioxide powder and MgH2 or CaH2. However, there is a problem that the silicon crystallite size rapidly increases due to a local exothermic reaction, magnesium and calcium are unevenly distributed, and the specific capacity retention rate of silicon dioxide decreases.
[0007] Patent Document 3 discloses a core-shell structure including a shell containing hollow carbon fibers and a core disposed in the hollow of the hollow carbon fibers, wherein the core contains a composite negative electrode active material including a first metal nanostructure, and a method for preparing the same.
[0008] Further, Patent Document 4 discloses a negative electrode active material containing first silicon oxide (SiO x , 0 < x < 2), and second silicon oxide (SiO y , 0 < y < 2) having a particle diameter smaller than the particle diameter (D90) of the first silicon oxide, wherein in the particle size distribution, the area ratio of the peak of the first silicon oxide to the peak of the second silicon oxide is 3 to 8.
[0009] Patent Document 5 discloses a negative electrode active material which is a powder having a cumulative 90% particle diameter (D 90 ) of 50 μm or less in the particle size distribution measured by laser diffraction scattering type particle size distribution, and containing fine powder A having a particle diameter of 2 μm or more and fine powder B having a particle diameter of less than 2 μm, wherein the fine powder A is silicon oxide and the fine powder B is silicon oxide.
[0010] However, these prior art documents relate to negative electrode active materials containing silicon and carbon, or negative electrode active materials in which the particle size distribution of silicon oxide is adjusted, but there is still a limit to simultaneously increasing the capacity, cycle characteristics, and initial efficiency of a secondary battery. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] JP 2002-042806 A [Patent Document 2] Japanese Patent No. 5406799 [Patent Document 3] JP 2014-67713 A [Patent Document 4] JP 2013-41826 A [Patent Document 5] JP 2015-164139 A Summary of the Invention [Problem to be solved by the invention]
[0012] An object of the present invention is to provide a silicon-silicon complex oxide-carbon composite material for use as a negative electrode active material in a lithium secondary battery, which can solve the problems of the prior art and improve not only the capacity of the lithium secondary battery but also the cycle characteristics and initial efficiency.
[0013] Another object of the present invention is to provide a method for preparing a silicon-silicon complex oxide-carbon composite material.
[0014] It is still another object of the present invention to provide a negative electrode active material and a lithium secondary battery including the same, each of which includes a silicon-silicon complex oxide-carbon composite material. [Means for solving the problem]
[0015] The present invention provides a silicon-silicon complex oxide-carbon composite material having a core-shell structure, wherein the core comprises silicon, a silicon oxide compound, and magnesium silicate, and the shell comprises a carbon layer, and the span value of the composite material in the following formula 1 is 0.6 to 1.5 when the particle sizes at which the cumulative volume concentration (%) in the particle size distribution is 10%, 50%, and 90% are D10, D50, and D90, respectively.
[0016] [Equation 1] Span = (D90-D10) / D50
[0017] Furthermore, the present invention Silicon powder and silicon oxide (SiO x , 0.5≦x≦2) a first step of preparing a raw material obtained using the powder; A second step of heating and evaporating the raw material and metallic magnesium at different temperatures, then depositing them and cooling them to obtain a silicon-silicon oxide composite material as a core; A third step of crushing and classifying the silicon-silicon composite oxide material to obtain a silicon-silicon composite oxide material powder; A fourth step of forming a carbon layer on the surface of the silicon-silicon composite oxide powder by chemical pyrolysis deposition to obtain a composite material having a core-shell structure; and A fifth step of subjecting the composite material having a core-shell structure to at least one step of pulverization and classification to obtain a silicon-silicon complex oxide-carbon composite material. The present invention provides a method for preparing a silicon-silicon complex oxide-carbon composite material, comprising:
[0018] The present invention further provides a negative electrode active material comprising the silicon-silicon complex oxide-carbon composite material.
[0019] The present invention further provides a lithium secondary battery comprising the negative electrode active material. Effect of the Invention
[0020] The silicon-silicon complex oxide-carbon composite material of this embodiment has a core-shell structure, the core comprises silicon, silicon oxide compound, and magnesium silicate, the shell comprises a carbon layer, and the particle size distribution of the composite material is adjusted to satisfy the span value of formula 1 in a specific range. Therefore, when used as the negative electrode active material of a secondary battery, it can improve not only the capacity but also the cycle characteristics and initial efficiency of the secondary battery. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1 is a graph showing the particle size distribution measurement results of the silicon-silicon complex oxide-carbon composite material of Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] The present invention is not limited to the following disclosure, but can be modified in various forms without departing from the spirit and scope of the invention.
[0023] In this specification, when a moiety is referred to as "comprising" an element, unless otherwise stated, it should be understood that the moiety may also include other elements.
[0024] Additionally, all numbers and formulas relating to quantities of ingredients, reaction conditions, and the like used herein should be understood as being modified by the term "about" unless otherwise specified.
[0025] In this specification, D10 is a value measured as the particle diameter at which the cumulative volume concentration (%) is 10% in particle size distribution measurement by a laser beam diffraction method.
[0026] In this specification, D50 is a value measured as the particle diameter at which the cumulative volume concentration (%) is 50% in particle size distribution measurement by a laser beam diffraction method.
[0027] In this specification, D90 is a value measured as the particle diameter at which the cumulative volume concentration (%) is 90% in particle size distribution measurement by a laser beam diffraction method.
[0028] The present invention will be described in detail below.
[0029] [Silicon-silicon complex oxide-carbon composite materials] A silicon-silicon complex oxide-carbon composite material (hereinafter referred to as "the composite material") according to one embodiment of the present invention has a core-shell structure, in which the core comprises silicon, a silicon oxide compound, and magnesium silicate, and the shell comprises a carbon layer. When the particle sizes at which the cumulative volume concentrations (%) in the particle size distribution are 10%, 50%, and 90% are D10, D50, and D90, respectively, the span value of the composite material in the following formula 1 is 0.6 to 1.5.
[0030] [Equation 1] Span = (D90-D10) / D50
[0031] The span value in Equation 1 is a measure of the particle size distribution ratio of the composite. That is, it is related to the percentage of particles with different particle diameters. If the composite has a high composition ratio of particles smaller than the average particle diameter to particles larger than the average particle diameter, it has a value greater than 1. If the composite is made up of only particles of the same size, the span value is 1.
[0032] Also, the smaller the span value in Equation 1, the narrower the particle size distribution.
[0033] The present composite material may have a span value of 0.6 to 1.3, or 0.8 to 1.1 in equation 1. When the span value of the present composite material of one embodiment of the present invention satisfies the above range, the viscoelasticity of the negative electrode active material composition (negative electrode slurry) prepared by using the present composite material, a binder, and a conductor material in combination becomes good, and the performance of the secondary battery can be improved.
[0034] Specifically, when applying the negative electrode active material composition to a current collector, for example, a copper thin film, appropriate viscoelasticity must be obtained to produce a negative electrode with a uniform coating amount. If the span value of Equation 1 is satisfied, as in the present composite material, a negative electrode active material with an appropriate level of viscoelasticity can be realized. As a result, a negative electrode with a uniform coating amount can be produced, which can prevent secondary batteries from igniting due to overcharging, and greatly contributes to improving the stability of secondary batteries. In addition, the density of the dry film obtained by applying the negative electrode active material composition can be increased, making it possible to realize a negative electrode with a structure that is almost not destroyed by contraction and expansion during charging and discharging of secondary batteries.
[0035] In addition, if the span value of Equation 1 satisfies the above range, a particle size distribution can be obtained in which the powder having a particle diameter larger than the average particle diameter of the composite material and the powder having a particle diameter smaller than the average particle diameter of the composite material have a narrow tail. In addition, a particle size distribution that is nearly symmetrical can be obtained. If the span value of Equation 1 is less than 0.6, the volume cumulative distribution curve of the composite material has a very sharp shape. The density of the dry film obtained by applying the negative electrode active material composition is reduced, and the capacity per unit volume of the secondary battery is reduced, which may result in a deterioration in cycle characteristics.
[0036] According to one embodiment of the present invention, the composite material may have a D10 of 0.7 μm to 4.0 μm, 1.0 μm to 4.0 μm, or 2.0 μm to 3.5 μm.
[0037] If the D10 of the composite material satisfies the above range, the content of the fine powder in the composite material is appropriate. Therefore, when applied to the negative electrode of a secondary battery, the viscosity of the negative electrode slurry containing the negative electrode active material can have a viscoelasticity that allows it to be applied immediately. In such a case, when the charge / discharge cycle of the secondary battery is repeated, the capacity retention rate is improved. In addition, fine particles with particularly small particle size among the negative electrode active material particles become contact points between the negative electrode active material particles, which produces the effect of improving the electrical conductivity and lithium desorption.
[0038] According to one embodiment of the present invention, the composite material may have a D50 of 0.5 μm to 10.0 μm, 1.0 μm to 8.0 μm, or 3.0 μm to 7.0 μm.
[0039] If the D50 of the composite material is within the above range, lithium ions are easily absorbed and released during charging and discharging, and particle damage is suppressed. If the D50 is 0.5 μm or more, the surface area per unit weight can be reduced, and the increase in irreversible capacity of the secondary battery can be suppressed. In addition, the BET specific surface area can be sufficiently reduced, thereby avoiding the adverse effects of an excessively large BET specific surface area. In addition, if the D50 is 10.0 μm or less, it can be immediately applied to the preparation of a negative electrode active material, which may be advantageous in terms of the process. In addition, if the D50 is controlled within the above range, uniform contraction and expansion can be ensured when the composite material is used as a negative electrode active material, and the cycle characteristics and initial efficiency of the secondary battery can be improved.
[0040] If D50 is more than 10.0 μm, the composite particles will expand rapidly due to charging of lithium ions, and the binding ability between the composite particles and between the particles and the current collector will decrease as charging and discharging are repeated, which may significantly reduce the life characteristics. There is also a concern that the activity may decrease due to a significant decrease in the specific surface area. If D50 is less than 0.5 μm, there is a concern that the dispersibility may decrease due to the aggregation of the composite particles in the preparation of the negative electrode active material composition using it.
[0041] According to one embodiment of the present invention, the composite material may have a D90 of 3.0 μm to 12.0 μm, 4.0 μm to 12.0 μm, or 4.0 μm to 10.0 μm.
[0042] If the D90 of the composite material satisfies the above range, it is possible to prevent the destruction of the conductive path due to the contraction and expansion during charging and discharging of the secondary battery. In addition, since the composite material does not contain excessively large particles, it is possible to improve the life characteristics of the secondary battery.
[0043] If D90 exceeds 12.0 μm, there is a risk that excessively large particles will be present in the composite material, which may undesirably damage the separator, whereas if D90 is less than 3.0 μm, there may be a problem of reduced packing density in the negative electrode of the secondary battery.
[0044] Furthermore, according to one embodiment of the present invention, the D10 and D90 ranges of the composite material may be close to the D50 range, respectively, in which case the particle size of the powder of the composite material is easier to control since the particle size distribution is narrower, and the composite material prepared can have a powder with a low level of agglomeration.
[0045] On the other hand, the present composite material may have a D90 / D10 of 1.0 to 5.0. Specifically, the D90 / D10 of the present composite material may be 2.0 to 4.5, specifically, 2.0 to 4.2 or 2.0 to 4.1. If the D90 / D10 is within the above range, the viscoelasticity of the negative electrode active material composition (negative electrode slurry) prepared by using the present composite material, a binder, and a conductor material in combination is good, and the performance of the secondary battery can be improved.
[0046] Furthermore, according to one embodiment of the present invention, the composite material may have a Dmin of 0.1 to 3.0 μm, 0.2 to 2.2 μm, or 0.2 to 2.0 μm. Dmin is a value measured as the particle size (particle diameter) at which the cumulative volume concentration is at a minimum. For example, in particle size distribution measurement by laser beam diffraction method, D 0.01 It is.
[0047] Further, the composite material may have a Dmax of 6.0 to 25 μm, 7 to 22 μm, or 7.45 to 21.9 μm, where Dmax is measured as the particle diameter at which the cumulative volume concentration is greatest, e.g., D99.9 when measuring particle size distribution by laser beam diffraction method.
[0048] When Dmin and Dmax each satisfy the above range, the packing density of the negative electrode active material of the secondary battery becomes maximum, and there can be advantages in that the printing characteristics of the negative electrode slurry, i.e., the uniformity of the thickness of the coating film when applied onto a current collector, and the ease of continuous printing are excellent.
[0049] Furthermore, the ratio of the difference between Dmax and Dmin to D50 ((Dmax-Dmin) / D50) may be 2.0 to 5.0, 2.0 to 4.0, or 2.2 to 3.7. The ratio of the difference between Dmax and Dmin to D50 indicates the content ratio of fine powder and coarse particle. If it is out of the above range, the coating workability of the negative electrode slurry is poor, and a uniform coating film cannot be obtained, which may cause a problem of a rapid deterioration in the life characteristics of the secondary battery.
[0050] This composite material has a density of 1.7 g / cm 3 ~2.6g / cm 3 , specifically, 2.0 g / cm 3 ~2.4g / cm 3 may have a specific gravity of
[0051] Specific gravity may refer to particle density, density, or true density. According to an embodiment of the present invention, the specific gravity may be measured using, for example, a dry density meter, such as Acupick II1340 manufactured by Shimadzu Corporation. The purge gas used may be helium gas, and the measurement may be performed after purging a sample holder set at a temperature of 23° C. 200 times.
[0052] The specific gravity of this composite material is 1.7g / cm 3 If the specific gravity is 2.6 g / cm or more, dissociation between the negative electrode active material powders caused by the volume expansion of the negative electrode active material during charging can be prevented, and cycle deterioration can be suppressed. 3 If the thickness is equal to or less than this, the impregnation of the electrolyte is improved and the utilization rate of the negative electrode active material is increased, so that the initial charge / discharge capacity can be improved.
[0053] In contrast, the specific gravity of this composite material is 1.7g / cm 3 If it is less than 2.6 g / cm, the rate characteristics of the secondary battery may deteriorate. 3 If the contact area exceeds this value, the contact area with the electrolyte increases, which may accelerate the decomposition reaction of the electrolyte or cause a side reaction in the battery.
[0054] In addition, the composite material is 2 / g~30m 2 / g, 3m 2 / g~25m 2 / g, or 3m 2 / g~20m 2 The composite material may have a specific surface area of 3 m 2 If the specific surface area of the composite material is less than 30 m / g, the surface activity is low and the binding strength of the binder during electrode preparation is weak. As a result, the cycle characteristics may decrease when the charge and discharge are repeated. 2 If the Cr content exceeds 1.0 / g, the amount of solvent absorbed during electrode preparation increases, and a large amount of binder may be required to maintain the binding properties. As a result, the conductivity may decrease, which may lead to a decrease in cycle characteristics. Furthermore, the contact area with the electrolyte increases, which may promote the decomposition reaction of the electrolyte or cause side reactions in the battery.
[0055] The specific surface area can be measured by the BET method using nitrogen adsorption, for example, using a specific surface area measuring device commonly used in the art (such as Macsorb HM (Model 1210) from MOUNTECH or Belsorp-mini II from Microtrac BEL).
[0056] The composite material may have a conductivity of 0.5 S / cm to 10 S / cm, specifically 0.8 S / cm to 8 S / cm, more specifically 0.8 S / cm to 6 S / cm. The conductivity of the negative electrode active material is an important factor in facilitating electron transfer in an electrochemical reaction. However, when preparing a high-capacity negative electrode active material using silicon or a silicon oxide compound, it is not easy to achieve an appropriate level of conductivity. Therefore, in one embodiment of the present invention, a negative electrode active material having a conductivity satisfying the above range can be provided by preparing the present composite material having a core-shell structure in which a shell containing a carbon layer is formed on the surface of a core containing silicon, a silicon oxide compound, and magnesium silicate. Furthermore, since the particle size distribution of the present composite material is controlled, the thickness expansion of the negative electrode active material can be suppressed, and as a result, the life characteristics and capacity of the secondary battery can be further improved.
[0057] The structure of the silicon-silicon complex oxide-carbon composite material will be described in detail below.
[0058] core The core of the silicon-silicon complex oxide-carbon composite material of one embodiment of the present invention comprises silicon, a silicon oxide compound, and magnesium silicate.
[0059] Silicon, silicon oxide compounds, and magnesium silicate are uniformly dispersed within the core of the silicon-silicon complex oxide-carbon composite material and firmly bonded to form the core, minimizing core fragmentation due to volume changes during charging and discharging.
[0060] On the other hand, a thin film containing silicon oxide (oxide film) may be formed on the surface of the silicon contained in this composite material. Since the surface of silicon is easily oxidized, it is necessary to reduce the amount of oxygen in the silicon as much as possible. In addition, even a very small amount of moisture remaining in this composite material is not preferable because it causes surface oxidation.
[0061] On the other hand, the oxide layer formed on the surface of the silicon reduces the reactivity between the negative electrode active material and the electrolyte, thereby suppressing the formation of a by-reaction product layer that may form on the surface of the negative electrode active material.
[0062] The content of silicon (Si) in the core may be 30% by weight to 80% by weight, specifically 40% by weight to 70% by weight, more specifically 40% by weight to 60% by weight, based on the total weight of the silicon-silicon complex oxide-carbon composite material. If the content of silicon is less than 30% by weight, the amount of active material for absorbing and releasing lithium is small, so that the charge and discharge capacity of the lithium secondary battery may decrease. If the content of silicon is more than 80% by weight, the charge and discharge capacity of the lithium secondary battery may increase, while the contraction and expansion of the electrode during charging and discharging may increase excessively, and the negative electrode active material powder may be further atomized, which may decrease the cycle characteristics.
[0063] On the other hand, the magnesium (Mg) content in the present composite material may be 2 wt% to 15 wt%, 2 wt% to 12 wt%, or 4 wt% to 10 wt%, based on the total weight of the silicon-silicon complex oxide-carbon composite material.
[0064] When the magnesium content is 2% by weight or more, the initial efficiency of the secondary battery can be improved. When the magnesium content is 15% by weight or less, it is advantageous in terms of the cycle characteristics and handling stability of the secondary battery. Furthermore, when the magnesium content satisfies the above range, the initial efficiency can be significantly increased to 85% or more, especially due to an increase in the Mg2SiO4 phase.
[0065] However, if the magnesium (Mg) content in the composite material is less than 2% by weight, the cycle characteristics of the secondary battery may be deteriorated, whereas if it exceeds 15% by weight, the charging capacity of the secondary battery may be deteriorated.
[0066] On the other hand, according to one embodiment of the present invention, the composite material may contain a metal other than magnesium. The other metal may be at least one selected from the group consisting of alkali metals, alkaline earth metals, Group 13-16 elements, transition metals, rare earth elements, and combinations thereof. Specific examples thereof include Li, Ca, Sr, Ba, Y, Ti, Zr, Hf, V, Nb, Cr, Mo, W, Fe, Pb, Ru, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ge, P, As, Sb, Bi, S, and Se.
[0067] According to one embodiment of the present invention, the magnesium content satisfies the above-mentioned range based on the total weight of the composite material, the crystallite size of the composite material including the carbon layer is 2 nm to 12 nm, and the composite material has a structure in which silicon is dispersed in a silicon oxide compound or magnesium silicate.
[0068] In this composite material, the core contains silicon, silicon oxide compound, and magnesium silicate, and the phase interfaces are in a bonded state, that is, each phase is dispersed with each other so that they are in a bonded state at the atomic level. Therefore, the volume change when lithium ions are absorbed and released is small, and no cracks are generated in the negative electrode active material even when charging and discharging are repeated. Therefore, there is no sudden decrease in capacity with respect to the number of cycles, so the cycle characteristics of the secondary battery can be excellent.
[0069] In addition, because the silicon, silicon oxide compound, and magnesium silicate phases are bonded at the atomic level, the desorption of lithium ions is promoted when the secondary battery is discharged, improving the balance between the charge and discharge amounts of lithium ions and increasing the charge and discharge efficiency. Here, the charge and discharge efficiency (%) means the ratio (y / x×100) of the discharge capacity (y) to the charge capacity (x), and indicates the proportion of lithium ions that can be released during discharge among the lithium ions absorbed in the negative electrode active material during charge.
[0070] The core of the composite material has an average particle diameter (D 50 ) The average particle diameter of the core (D 50 If the average particle diameter (D ) is less than 0.5 μm, the bulk density may be too small, resulting in a decrease in the charge / discharge capacity per unit volume. 50 If the thickness exceeds 10 μm, preparation of the electrode layer becomes difficult, and the electrode layer may peel off from the current collector.
[0071] The average particle diameter of the core (D 50 ) can be achieved by grinding the core particles. Also, the average particle diameter (D 50), classification may be performed to adjust the particle size distribution, and dry classification, wet classification, or sieve classification (filtration) can be used. In dry classification, the steps of dispersion, separation (separation of fine particles and defective particles), recovery (separation of solids and gas), and discharge are performed sequentially or simultaneously using an air flow, and pretreatment (adjustment of moisture, dispersibility, humidity, etc.) is performed prior to classification to adjust the humidity or oxygen concentration of the air flow used so as not to reduce the classification efficiency due to interference between particles, particle shape, air flow turbulence, velocity distribution, static electricity, etc. Also, by performing crushing and classification at the same time, the desired particle size distribution can be obtained.
[0072] If the core particles have an average particle diameter of 0.5 μm to 10 μm by the grinding and classification process, the initial efficiency or cycle characteristics can be increased by about 10% to 20% compared to before classification. The core particles at the time of grinding and classification may have a Dmax of about 10 μm or less. In such a case, the specific surface area of the core particles may be reduced, and as a result, the amount of lithium added to the solid electrolyte interface (SEI) layer may be reduced.
[0073] According to one embodiment, closed pores or voids are introduced into the core, and silicon, silicon oxide compounds, and magnesium silicate are simultaneously used to form a core structure in which the silicon, silicon oxide compounds, and magnesium silicate are uniformly dispersed at the atomic level. The size of each particle of silicon, silicon oxide compounds, and magnesium silicate in the core can be finely divided. If the size of each particle of silicon, silicon oxide compounds, and magnesium silicate is too large, they are unlikely to exist inside the core, and cannot fully function as the core.
[0074] The composite material contains a core, which suppresses volume expansion and prevents or reduces side reactions with the electrolyte, thereby improving the discharge capacity, life characteristics, and thermal stability of the secondary battery.
[0075] Each component included in the core will be described in detail below.
[0076] Silicon Since the core in the silicon-silicon complex oxide-carbon composite material contains silicon, it can achieve high capacity when applied to secondary batteries.
[0077] Silicon may also be formed by dispersing it in a silicon oxide compound or magnesium silicate.
[0078] Since silicon charges lithium, if silicon is not used, the capacity of the secondary battery may decrease. Silicon may be crystalline or amorphous, specifically, amorphous or a phase close to it. When silicon is crystalline, the dimensions of the crystallites are small, so the density of the matrix can be increased, the strength can be strengthened, and cracks can be prevented. Therefore, the initial efficiency and cycle life characteristics of the secondary battery can be further improved. In addition, when silicon is amorphous or a phase close to it, the expansion or contraction during charging and discharging of the lithium secondary battery is small, and the battery performance such as capacity characteristics can be further improved.
[0079] Silicon has high initial efficiency and battery capacity, but undergoes very complex crystal changes as it electrochemically absorbs, stores, and releases lithium atoms. As the electrochemical reactions of absorbing, storing, and releasing lithium atoms progress, the composition and crystal structure of silicon change to Si (crystal structure: Fd3m), LiSi (crystal structure: 141 / a), Li2Si (crystal structure: C2 / m), Li7Si2 (Pbam), Li 22 S 15 (F23), etc. In addition, the volume of silicon can expand by about four times (400%) due to changes in the complex crystal structure. Therefore, as charging and discharging are repeated, silicon is destroyed and bonds between lithium atoms and silicon are formed. As a result, the insertion sites of lithium atoms that silicon originally had are damaged, and the cycle life is significantly reduced.
[0080] Silicon can be uniformly distributed within the composite material, in which case superior mechanical properties, such as strength, can be achieved.
[0081] The composite material may have a structure in which silicon is uniformly dispersed in a silicon oxide compound or magnesium silicate. Since silicon is dispersed so as to surround magnesium silicate, the expansion and contraction of silicon can be suppressed, and high performance of the secondary battery can be obtained.
[0082] In the composite material of one embodiment of the present invention, silicon may have a crystallite size of 2 nm to 20 nm, 2 nm to 12 nm, or 2 nm to 10 nm, as calculated using the Scherrer equation based on the full width at half maximum of the Si(220) diffraction peak at about 2θ=47.5°, when subjected to X-ray diffraction (Cu-Kα) analysis using copper as a cathode target.
[0083] Furthermore, the silicon contained in the composite material may be amorphous, crystalline with a crystallite size of 2 nm to 20 nm, or a mixture thereof. Although it is preferable that the silicon is close to 100% amorphous, it may be a mixture of amorphous and crystalline since it is difficult to obtain completely amorphous silicon in the process. Even in such a case, the proportion of amorphous silicon is preferably 50% or more. When the silicon is amorphous, crystalline with a crystallite size in the above range, or a mixture thereof, cracks during the first charge and discharge of the secondary battery can be suppressed. If some cracks occur during the first charge and discharge, these become the starting point, and the cracks expand during repeated charge and discharge, leading to large cracks. Therefore, if the silicon is outside the above range, problems may occur in the performance of the secondary battery. Also, if the silicon is amorphous or crystalline with a crystallite size in the above range, damage due to volume expansion caused by repeated charge and discharge can be mitigated.
[0084] If the silicon crystallite size is less than 2 nm, the charge / discharge capacity of the secondary battery may decrease, or the characteristics may change due to increased reactivity during storage, which may cause problems in the process.
[0085] In addition, when the crystallite size of silicon is 2 nm or more, there is almost no concern about a decrease in charge-discharge capacity. When the crystallite size of silicon is 20 nm or less, the possibility of the occurrence of a region that does not contribute to discharge is low, and a decrease in Coulomb efficiency, which is the ratio of charge capacity to discharge capacity, can be suppressed.
[0086] In addition, when silicon is fine particles, it is preferable to form a lithium alloy with a large specific surface area, thereby suppressing bulk destruction. The silicon fine particles react with lithium during charging to form Li 4.2 Si, and return to silicon during discharge. In such a case, when X-ray diffraction is frequently performed on the silicon fine particles, the silicon may show a broad pattern and its structure may change to amorphous silicon.
[0087] When the silicon fine particles are further atomized into an amorphous or finer crystallite size, the density of the composite material increases, thereby approaching the theoretical density and significantly reducing pores. As a result, the density of the matrix can be increased, the strength can be enhanced to prevent cracks, and the characteristics of the initial efficiency and cycle life of the secondary battery can be further improved.
[0088] Silicon oxide compound Since the silicon-silicon complex oxide-carbon composite material contains a silicon oxide compound, when applied to a secondary battery, the capacity can be increased and volume expansion can be suppressed.
[0089] The silicon oxide compound can be a silicon-based oxide represented by the formula SiO x (0 < x ≤ 1.5). Specifically, the silicon oxide compound can be SiO x (0.8 < x ≤ 1.2), and more specifically, SiO x (0.9 < x ≤ 1.1). In the formula SiO x , when x is less than 0.5, the preparation of SiO x may be difficult. When x exceeds 1.5, the proportion of inert silicon dioxide generated during heat treatment increases, and there is a concern that the charge-discharge capacity may decrease when used in a lithium secondary battery.
[0090] The silicon oxide compound may be amorphous, and when observed under a transmission electron microscope, may have a structure in which silicon is distributed in the amorphous silicon oxide compound.
[0091] The silicon oxide compound can be obtained by a method including cooling and condensing the silicon oxide gas produced by heating a mixture of silicon powder and silicon oxide powder (or silicon dioxide powder).
[0092] The silicon oxide compound may be used in an amount of 5 mol % to 45 mol % based on the total weight of the silicon-silicon complex oxide-carbon composite material.
[0093] If the content of the silicon oxide compound is less than 5 mol %, the volume expansion and life characteristics of the secondary battery may deteriorate, whereas if it exceeds 45 mol %, the initial irreversible reaction of the secondary battery may increase.
[0094] Meanwhile, in the case of negative electrode active materials containing silicon and silicon oxide compounds, a thick non-conductive by-product (SEI) layer may form on the surface of the negative electrode active material due to continuous reactions with the electrolyte during charging and discharging of the secondary battery. As a result, the negative electrode active material may be electrically short-circuited within the electrode, deteriorating the life characteristics, or the by-product layer may cause further volume expansion of the electrode.
[0095] Therefore, it is necessary to reduce the reactivity between the negative electrode active material and the electrolyte and to minimize the formation of a by-reaction product layer that may be formed on the surface of the negative electrode active material. For this purpose, it is necessary to control the oxygen content on the surface of silicon or silicon oxide compound particles as low as possible.
[0096] To this end, in the present composite material containing silicon, a silicon oxide compound, and magnesium silicate, the ratio of the number of oxygen atoms to the number of silicon atoms (O / Si) may be 0.45 to 1.2. Specifically, the ratio of the number of oxygen atoms to the number of silicon atoms (O / Si) may be 0.45 to 1.0 or 0.45 to 0.80. It is preferable that O / Si is low. In such a case, the active phase originating from silicon increases, and therefore the initial charge / discharge capacity can be improved.
[0097] On the other hand, as the silicon content increases, the rate of volume expansion (expansion rate) due to silicon increases, which undesirably increases the formation of cracks. To reduce the formation of cracks, it is necessary to increase the strength of the matrix by forming pores in the composite material or by using a strong binder. In order to reduce the O / Si ratio, it is preferable to reduce the ratio of silicon oxide or silicon dioxide as much as possible to increase the charge / discharge capacity or cycle characteristics.
[0098] If the O / Si ratio is less than 0.45, the process may be hindered, silicon clusters may be formed, and the secondary battery may expand easily during charging, resulting in a deterioration in cycle characteristics. On the other hand, if the O / Si ratio exceeds 1.2, the specific gravity of the inactive silicon dioxide, silicon oxide, or magnesium silicate may increase, and there is a concern that the charge / discharge capacity may decrease. In addition, the SiO2 layer formed on the surface of the silicon oxide may become thick, resulting in a decrease in the conductivity of the silicon oxide. As a result, when used as the negative electrode active material of a lithium secondary battery, sufficient current does not flow, and the internal resistance of the battery increases due to the resistance of the negative electrode, and the performance of the lithium secondary battery thus produced may be significantly reduced.
[0099] Magnesium Silicate The core of this composite material contains magnesium silicate, so when applied to secondary batteries, it can improve charge / discharge capacity characteristics and cycle characteristics.
[0100] Since magnesium silicate hardly reacts with lithium ions during charging and discharging of a secondary battery, it can reduce the expansion and contraction of the electrode when lithium ions are absorbed in the electrode, thereby improving the cycle characteristics of the secondary battery. Furthermore, the strength of the matrix, which is the continuous phase surrounding the silicon fine particles, can be strengthened by magnesium silicate.
[0101] Magnesium silicate can be represented by the following formula 1:
[0102] [ka]
[0103] The magnesium silicate may include at least one selected from MgSiO3 crystals (enstatite) and Mg2SiO4 crystals (forsterite).
[0104] Furthermore, according to one embodiment, the magnesium silicate may include MgSiO3 crystals and may further include Mg2SiO4 crystals.
[0105] Furthermore, according to one embodiment, the magnesium silicate contains MgSiO3 crystals and further contains Mg2SiO4 crystals. In such a case, in an X-ray diffraction analysis, the ratio IF / IE of the intensity of the X-ray diffraction peak corresponding to the Mg2SiO4 crystals appearing in the range of 2θ=22.3° to 23.3° to the intensity of the X-ray diffraction peak corresponding to the MgSiO3 crystals appearing in the range of 2θ=30.5° to 31.5° may be greater than 0 and less than or equal to 1.
[0106] Furthermore, the magnesium silicate may contain a substantially large amount of MgSiO3 crystals to enhance charge / discharge capacity and initial efficiency.
[0107] As used herein, the phrase comprising a "substantially major amount" of an ingredient can mean comprising that ingredient as a major component or comprising primarily that ingredient.
[0108] Magnesium silicate, SiO x The content of magnesium relative to SiO can affect the initial discharge characteristics or cycle characteristics during charging and discharging. x The silicon in the battery can be alloyed with lithium atoms to improve the initial discharge characteristics. Specifically, the use of a large amount of MgSiO3 crystals in magnesium silicate can improve the cycle performance during charging and discharging.
[0109] When magnesium silicate contains both MgSiO3 and Mg2SiO4 crystals, it can increase the initial efficiency. If more Mg2SiO4 crystals are used than MgSiO3 crystals, the degree of alloying between silicon and lithium atoms may decrease, which may result in a decrease in the initial discharge characteristics.
[0110] When the magnesium silicate contains both MgSiO3 crystals and Mg2SiO4 crystals, it is preferred that the MgSiO3 crystals and Mg2SiO4 crystals are uniformly dispersed in the core. Their crystallite size may be 30 nm or less, specifically 20 nm or less.
[0111] The silicon in magnesium silicate reacts with lithium during charging to form Li 4.2 Si and returns to silicon upon discharge. The capacity of the secondary battery may decrease due to the capacity change during repeated charging and discharging. However, the volume change rate of MgSiO3 crystals is smaller than that of Mg2SiO4 crystals, so the cycle characteristics of the secondary battery can be further improved. Furthermore, MgSiO3 crystals and Mg2SiO4 crystals can act as diluents or inactive materials in the negative electrode active material.
[0112] According to one embodiment, magnesium is SiO x For example, when SiO reacts with magnesium, as the doping amount of magnesium increases, the reaction may proceed in the order of the following reaction schemes 1 to 3.
[0113] [ka]
[0114] In the above reaction, the production mechanism of MgSiO3(s) and Mg2SiO4(s) can be represented as the following reaction schemes 4 to 6.
[0115] [ka]
[0116] Specifically, when the content of Mg relative to SiO is 1 / 3 mol%, the reaction occurs as shown in Reaction Scheme 4, forming Si phase, MgSiO3, and unreacted SiO until the content reaches 1 / 3 mol%. When the content is 1 / 3 mol%, Si and MgSiO3 can be formed.
[0117] As mentioned above, as the doping amount of magnesium increases, a large amount of Mg2SiO4 can be formed, but on the other hand, the crystallite size of silicon can also increase. It is understood that since the molar ratio of magnesium to silicon is large, the amount of evaporation of magnesium increases, and the reaction temperature increases accordingly, thereby increasing the crystallite size of silicon. As the crystallite size increases, the amount of silicon that should be alloyed with lithium atoms decreases, which may reduce the initial efficiency of the secondary battery. Therefore, excessive production of Mg2SiO4 may be undesirable. At the same time, the added silicon atoms and magnesium atoms react to form Mg2SiO4, which hardly reacts with lithium atoms, which may reduce the initial efficiency of the secondary battery.
[0118] On the other hand, when more MgSiO3 than Mg2SiO4 is formed in magnesium silicate, the ratio of magnesium to silicon is smaller, so that the temperature rise due to the evaporation of Mg can be reduced. As a result, the growth of silicon can be suppressed, so that the crystallite size can be 20 nm or less, and the cycle characteristics and initial efficiency of the secondary battery can be improved.
[0119] On the other hand, since SiO is a mixture of Si and SiO2 (1 / 2Si + 1 / 2SiO2) as shown in the following Reaction Scheme 7, in the actual reaction, SiO2 can be produced by a disproportionation reaction.
[0120] [ka]
[0121] In Reaction Scheme 7, the SiO2 produced by the disproportionation reaction may react with Li to cause an irreversible reaction and form lithium silicate, thereby reducing the initial efficiency.
[0122] For example, when 0.4 moles of Mg are added to 1 mole of SiO, the content of Mg is 18% by weight. Since the element concentration distribution is uniform, reactions according to the content of Mg can occur. As mentioned above, MgSiO3 and Mg2SiO4 can be formed as Mg-containing compounds simultaneously with the formation of Si.
[0123] As mentioned above, the doping amount of magnesium is important for the formation of MgSiO3 crystals and Mg2SiO4 crystals, but the uniformity of magnesium element concentration distribution may also be important. If the magnesium element concentration distribution is not uniform, silicon dioxide (SiO2) may be formed, which is undesirable. Furthermore, if silicon dioxide, metallic magnesium, or MgSi alloy is formed in the core of the composite material, the initial efficiency or capacity retention of the secondary battery may decrease. Therefore, the performance of the secondary battery can be improved by making the magnesium element concentration distribution uniform.
[0124] Specifically, in the present composite material, the ratio of Mg atoms to Si atoms in the silicon-silicon composite oxide, i.e., Mg atoms:Si atoms, may be an atomic ratio of 1:1 to 1:100. Specifically, the atomic ratio of Mg atoms:Si atoms may be 1:1 to 1:50, 1:2 to 1:50, or 1:2 to 1:20. When the atomic ratio of Mg to Si is less than the above range (when the amount of Mg added is excessively large), an excessive amount of Mg2SiO4 can be formed, which can increase the initial charge-discharge efficiency, but on the other hand, may deteriorate the charge-discharge cycle characteristics. Also, when the atomic ratio of Mg atoms to Si atoms exceeds the above range (when the amount of Si added is excessively large), the effect of improving the initial efficiency may be small.
[0125] The composite material according to one embodiment may have a peak of MgSiO3 crystals appearing in the diffraction angle range of 30.5°≦2θ≦31.5° in X-ray diffraction analysis. Furthermore, the composite material may have a peak of Mg2SiO4 crystals appearing in the diffraction angle range of 22.3°≦2θ≦23.3° in X-ray diffraction analysis.
[0126] For example, for MgSiO3 crystals, if a line is drawn between the diffraction intensity at 2θ = 31.8° and the diffraction intensity at 2θ = 33.8°, and the straight line is the base intensity, then if the ratio of the maximum intensity P1 at 2θ = 32.8 ± 0.2° to the base intensity B1 at the maximum intensity angle is P1 / B1 > 1.1, it can be determined that MgSiO3 crystals are present.
[0127] For example, for Mg2SiO4, if a line is drawn between the diffraction intensity at 2θ=31.3° and the diffraction intensity at 2θ=33.3°, and the straight line is the base intensity, then if the ratio of the maximum intensity P2 at 2θ=32.3±0.3° to the base intensity B2 at the maximum intensity angle is P2 / B2>1.1, it can be determined that Mg2SiO4 crystals are present.
[0128] In one embodiment, the core of the composite material contains magnesium silicate, so that even if the lithium ions increase rapidly during charging and discharging, the core hardly reacts with the lithium ions, which reduces the degree of expansion and contraction of the electrode. As a result, the cycle characteristics of the secondary battery can be improved. In addition, since the core of the composite material contains magnesium silicate, the irreversible capacity is small, and the charge and discharge efficiency can be improved.
[0129] shell The shell of the silicon-silicon complex oxide-carbon composite material of the present invention includes a carbon layer (carbon film), which allows a secondary battery with high capacity to be realized. In particular, it can solve the problems of volume expansion and stability loss that may occur when silicon is used, and can increase electrical conductivity.
[0130] In the present composite material, it is preferable that the carbon layer is formed uniformly over the entire surface of the core in order to further increase the electrical conductivity. If a uniform carbon coating is formed, it is possible to suppress the occurrence of cracks caused by stress generation due to the rapid volume expansion of silicon. Since the cracks occur irregularly, there may be areas that are electrically shorted, which may result in a defective battery. Therefore, if the carbon layer is formed uniformly, it is possible to improve the initial efficiency and life characteristics of the negative electrode active material.
[0131] Specifically, a shell in which a conductive carbon layer is formed on a part or the entire surface, specifically on the entire surface of each of the silicon, silicon oxide compound, and magnesium silicate contained in the core of the composite material, is used, thereby making it possible to increase electrical conductivity.
[0132] For example, the core may have a structure in which amorphous silicon having dimensions of several nanometers to several tens of nanometers is finely dispersed in a silicon oxide compound or magnesium silicate. In general, silicon oxide compounds have the advantage of having a battery capacity 5 to 6 times that of silicon or carbon and small volume expansion, but on the other hand, they have problems in that they have a large irreversible capacity due to irreversible reactions, a short lifespan, and a very low initial efficiency of 70% or less. Here, the irreversible reaction means that Li-Si-O or Si+Li2O is formed by reaction with lithium ions during discharge. The problems of a short lifespan and low initial efficiency may be due to a decrease in the diffusion rate of lithium atoms, that is, a decrease in electrical conductivity, due to low structural stability during charging and discharging.
[0133] Thus, the composite material of one embodiment of the present invention has a core-shell structure with a shell formed of a carbon layer formed by coating the surface of the composite core with carbon to solve the problem of reduced electrical conductivity.
[0134] In addition, since a shell is formed on the surface of the core, side reactions with the silicon contained in the core and with the electrolyte can be prevented, and contamination of silicon, silicon oxide compounds, and magnesium silicate can be prevented or reduced.
[0135] In addition, the carbon layer of the shell may be formed uniformly and thinly to further increase the electrical conductivity, which can further improve the initial efficiency and life characteristics of the secondary battery.
[0136] According to one embodiment of the present invention, once a core is produced in which a uniform carbon layer is formed on each surface of silicon, silicon oxide compound, and magnesium silicate, a so-called double-structure carbon layer can be formed in which a thin and uniform carbon layer is formed as a shell on the surface of the core. When a double-structure carbon layer is formed, it has the effect of preventing each of silicon, silicon oxide compound, and magnesium silicate from being exposed to the outside. The so-called double-structure carbon layer can be formed, for example, by repeatedly performing carbon deposition several times. Then, a double carbon layer having a shell function is formed on the surface of the core on which the carbon layer is formed, so that each particle can be prevented from being exposed to the outside. In such a case, electrical connection can be maintained despite the volume change of silicon, silicon oxide compound, or magnesium silicate during charging and discharging. Furthermore, even if a crack occurs on the surface of the carbon layer, electrical connection with the carbon layer can be maintained as long as the carbon layer is not completely separated.
[0137] The method for coating the core surface with carbon may be a method of chemical vapor deposition (CVD) of the silicon-silicon oxide composite core in organic gas and / or vapor, or a method of introducing organic gas and / or vapor into a reactor during heat treatment.
[0138] Furthermore, not only does the thickness of the carbon layer or the amount of carbon affect the electrical conductivity, but the uniformity of the layer can also be important. For example, even if a sufficient amount of carbon is obtained, if the film is not uniform, so that the silicon oxide surface is partially exposed or partly insulating, the charge / discharge capacity or cycle characteristics of the secondary battery may be adversely affected.
[0139] The electrical conductivity of the carbon can be adjusted by selecting the type of carbon source material, the type and content of the mixed gas, and the reaction time and reaction temperature.
[0140] According to one embodiment, the content of carbon (C) may be 2 wt% to 30 wt%, 2 wt% to 15 wt%, or 4 wt% to 10 wt%, based on the total weight of the silicon-silicon complex oxide-carbon composite material.
[0141] If the carbon (C) content is less than 2% by weight, the electrical conductivity cannot be sufficiently improved, and there is a concern that the electrode life of the lithium secondary battery may be shortened. Also, if the carbon (C) content exceeds 30% by weight, the discharge capacity of the secondary battery may decrease, and the bulk density may decrease, so that the charge / discharge capacity per unit volume may decrease.
[0142] The carbon layer may have an average thickness of 1 nm to 300 nm, specifically 5 nm to 200 nm or 10 nm to 150 nm, more specifically 10 nm to 100 nm. When the carbon layer has a thickness of 1 nm or more, the electrical conductivity can be improved. When the carbon layer has a thickness of 300 nm or less, the capacity reduction of the secondary battery can be suppressed.
[0143] The average thickness of the carbon layer can be measured, for example, by the following procedure.
[0144] First, the negative electrode active material is observed at an arbitrary magnification using a transmission electron microscope (TEM). The magnification is preferably such that it can be confirmed with the naked eye. Next, the thickness of the carbon layer is measured at 15 arbitrary points. In this case, it is preferable to randomly select measurement positions as widely as possible without concentrating on a specific area. Finally, the average value of the thickness of the carbon layer at the 15 points is calculated.
[0145] The carbon layer may include at least one selected from the group consisting of graphene, reduced graphene oxide, carbon nanotubes, and carbon nanofibers. Specifically, it may include graphene. Further, the carbon layer may include graphite.
[0146] The carbon film can enhance electrical contact between particles while maintaining the appearance of the shell, and can also ensure excellent conductivity even after the electrode expands during charging and discharging, further improving the performance of secondary batteries.
[0147] [Method for preparing silicon-silicon complex oxide-carbon composite material] According to one embodiment of the present invention, a method for preparing a silicon-silicon complex oxide-carbon composite material is provided.
[0148] The method for preparing the silicon-silicon complex oxide-carbon composite material of the present invention comprises the steps of: x The method includes a first step of preparing a raw material obtained using a magnesium oxide powder (0.5≦x≦2), a second step of heating and evaporating the raw material and metallic magnesium at different temperatures, subsequently adhering them, and cooling them to obtain a silicon-silicon composite oxide core, a third step of pulverizing the silicon-silicon composite oxide composite to an average particle diameter of 0.5 μm to 10 μm and classifying it to obtain a silicon-silicon composite oxide powder, a fourth step of forming a carbon layer on the surface of the silicon-silicon composite oxide powder by a chemical pyrolysis deposition method to obtain a composite material having a core-shell structure, and a fifth step of subjecting the composite material having a core-shell structure to at least one of pulverizing and classifying steps to obtain a silicon-silicon complex oxide-carbon composite material.
[0149] Specifically, in the method for preparing the composite material, the first step may include preparing a raw material obtained by using silicon powder and silicon oxide powder.
[0150] The raw material may be a mixture obtained by mixing silicon powder and silicon oxide powder, or a compound obtained by heating the mixture, cooling the gas generated thereby, and condensing the gas. The mixture and the compound may also be used as a blend.
[0151] Specifically, according to one embodiment of the present invention, a mixture obtained by mixing silicon powder and silicon oxide powder can be used as the raw material.
[0152] Silicon oxide powder is SiO x where x may be 0.5 to 2. The mixing can be carried out by mixing silicon powder and silicon oxide powder so that the molar ratio of oxygen element per mole of silicon element in the mixture is 0.8 to 1.2. Specifically, silicon powder and silicon oxide powder can be mixed in a molar ratio of 0.9 to 1.1 oxygen element per mole of silicon element.
[0153] For example, the mixing can be carried out in a molar ratio of 0.8 to 1.2 of silicon oxide powder per 1 mole of silicon powder.
[0154] In addition, when mixing silicon powder and silicon dioxide powder, taking into consideration the surface oxygen of the silicon powder and the presence of trace oxygen in the reactor, the ratio may be 0.9 to 1.1 mol or 0.95 to 1.05 mol of silicon dioxide powder per 1 mol of silicon powder. Also, a mixed granular raw material obtained by compounding, mixing, granulating, and drying silicon powder and silicon dioxide powder may be used.
[0155] According to another embodiment of the present invention, a compound obtained by a method including mixing and heating silicon powder and silicon oxide powder, and cooling and condensing the silicon oxide gas thus produced may be used as the raw material, and this compound is SiOx (0.9≦x≦1.1).
[0156] The reaction for producing silicon oxide gas may be carried out by heating the raw material for condensation under reduced pressure. The reaction temperature may be 1,000°C or higher, for example, 1,200°C to 1,500°C.
[0157] On the other hand, the deposition apparatus for cooling and recovering the silicon oxide gas may be maintained at a low temperature of 25° C. to 80° C. The silicon oxide gas is cooled and maintained at a low temperature after cooling, so that a homogenized amorphous silicon oxide compound can be coagulated and generated. As a result, the silicon oxide compound can be preferably obtained by recovering and pulverizing the coagulated product.
[0158] In addition, when a mixture of silicon powder and silicon oxide powder is used as the raw material powder, silicon oxide SiO x If x is less than 0.5 in the formula, then a suitable amount of silicon dioxide powder may be further added to adjust the value of x to within the range of 0.5 to 2.
[0159] In addition, when the mixture and the compound can be used as a blend, the mixture and the compound can be mixed so that the molar ratio of oxygen element per mole of silicon element in the blend is 0.8 to 1.2. Specifically, the mixture and the compound can be mixed at a molar ratio of oxygen element per mole of silicon element of 0.9 to 1.1.
[0160] Furthermore, the raw material has a molar ratio of oxygen element per 1 mole of silicon element of 0.8 to 1.2.
[0161] If the molar ratio of oxygen element per mole of silicon element in the raw material in the first step is less than 0.8 or more than 1.2, a large amount of reaction residue will remain after the reaction in the second step, reducing the production yield.
[0162] Additionally, when a blend of the mixture and the compound is used, the compound may be further added in an amount of from 20% by weight to less than 100% by weight based on the total weight of the blend.
[0163] On the other hand, the average particle diameter of the silicon powder and silicon oxide powder used as raw materials is not particularly limited.For example, the average particle diameter of the silicon powder may be 5 μm to 50 μm, 10 μm to 40 μm, or 15 μm to 30 μm, and the average particle diameter of the silicon oxide powder may be 5 nm to 50 nm, 10 nm to 40 nm, or 15 nm to 30 nm.
[0164] When a powder having an average particle diameter within the above range is used, the deposition and evaporation of silicon oxide becomes uniform, and fine silicon can be obtained.
[0165] In the method for preparing the composite material, the second step may include heating and evaporating the raw material and metallic magnesium at different temperatures, followed by depositing them and cooling them to obtain a silicon-silicon oxide composite material (composite material A).
[0166] The raw material and metallic magnesium may be placed in a crucible in a vacuum reactor and heated and evaporated at different temperatures.
[0167] The thermal evaporation of the raw material in the second step may be carried out at 900°C to 1,800°C, 1,000°C to 1,600°C, or 1,200°C to 1,600°C under a pressure of 0.0001 Torr to 2 Torr. If the temperature is lower than 900°C, it may be difficult to carry out the reaction, thereby reducing productivity. If the temperature exceeds 1,800°C, the reactivity may decrease.
[0168] The heating and evaporation of the metallic magnesium in the second step may be carried out at a temperature of 500° C. to 1100° C., 600° C. to 1000° C., or 650° C. to 900° C. under a pressure of 0.0001 Torr to 2 Torr.
[0169] If the heating and evaporation of the raw material and the metallic magnesium satisfy the above ranges, fine silicon and fine magnesium silicate can be produced, thereby obtaining the desired SiO x It is possible to obtain a silicon oxide compound having a composition (0.5≦x≦1.5).
[0170] On the other hand, the deposition in the second step may be carried out at a temperature of 300°C to 800°C, specifically 400°C to 700°C.
[0171] The cooling may be performed by quenching to room temperature with water cooling, or may be performed at room temperature while injecting an inert gas. The inert gas may be at least one selected from carbon dioxide gas, argon (Ar), helium (He), nitrogen (N2), and hydrogen (H2).
[0172] In the present invention, the raw material and metallic magnesium are heated to evaporate, and then deposited on the substrate in the reactor, so that the silicon-silicon composite oxide complex can be synthesized by a uniform gas-phase reaction of the particles, thereby preventing the rapid growth of silicon caused by an exothermic reaction when magnesium is mixed locally in excess, as in a solid-state reaction.
[0173] In the present method for preparing a composite material, the third step may include pulverizing the silicon-silicon composite oxide composite material to an average particle diameter of 0.5 μm to 10 μm and classifying the same to obtain a silicon-silicon composite oxide composite material powder (composite material B).
[0174] More specifically, the average particle diameter (D 50 ) may be pulverized to a size of 2 μm to 10 μm, specifically 3 μm to 8 μm.
[0175] The grinding may be performed using a grinding device well known in the art, for example, at least one selected from the group consisting of a jet mill, a ball mill, a stirring media mill, a roll mill, a hammer mill, a pin mill, a disk mill, a colloid mill, and an atomizer mill.
[0176] Specifically, the grinding can be performed using a ball mill or stirring media mill, which moves grinding media such as balls or beads and grinds the object to be ground using impact, friction, or compression force provided by kinetic energy, or a roll mill, which grinds the object to be ground using compression force from rollers. In addition, a jet mill may be used, which collides the object to be ground with an internal material or with each other at high speed and grinds the object using the impact force provided by the collision. Furthermore, the object to be ground can be ground using an impact force provided by the rotation of a rotor equipped with a hammer, blade, or pin, using a hammer mill, pin mill, or disk mill. In addition, a colloid mill or atomizer mill using shear force may be used as a high-pressure wet counter-impact type disperser.
[0177] Moreover, classification may be performed using at least one method selected from dry classification, wet classification, and sieve classification.
[0178] According to one embodiment of the present invention, a dry classifier equipped with a cyclone can be used in conjunction with a jet mill.
[0179] In jet mills, the steps of dispersion, separation (separation of fine particles from defective particles), recovery (separation of solids from gas), and discharge can be carried out sequentially using airflow. In such cases, the classification efficiency must not be reduced by the effects of particle-particle interference, particle shape, airflow turbulence, velocity distribution, and static electricity.
[0180] That is, the airflow used is pretreated before classification (adjusting moisture, dispersibility, humidity, etc.) to adjust the moisture and oxygen concentrations. In addition, in dry types with an integrated classifier such as a cyclone, pulverization and classification are carried out at the same time, making it possible to achieve the desired particle size distribution.
[0181] In the preparation method of this composite material, the fourth step may include forming a carbon layer on the surface of the silicon-silicon oxide composite powder by chemical pyrolysis deposition to obtain a composite material having a core-shell structure.
[0182] In this process, a carbon layer is formed on the surface of the silicon-silicon oxide composite material, which is thought to enhance the electrical contact between the particles. It can also provide excellent conductivity even after the electrode expands due to charging and discharging, further improving the performance of the secondary battery.
[0183] The carbon layer can increase the electrical conductivity of the negative electrode active material to improve the output characteristics and cycle characteristics of the secondary battery, and can increase the stress relaxation effect when the volume of the negative electrode active material changes.
[0184] When forming a carbon layer on the surface of the silicon-silicon oxide composite powder by chemical pyrolysis deposition, the type of carbon source material, the type and content of mixed gas, reaction time and reaction temperature can be selected and adjusted respectively.
[0185] The carbon layer may include at least one selected from the group consisting of graphene, reduced graphene oxide, carbon nanotubes, and carbon nanofibers.
[0186] The step of forming the carbon layer can be carried out by injecting at least one carbon source gas selected from the compounds represented by the following formulas 2 to 4, and reacting the silicon-silicon oxide composite material obtained in the third step in a gaseous state at 600°C to 1,200°C.
[0187] [ka]
[0188] Also, in formula 4, x may be the same as or smaller than y.
[0189] The compound represented by formula 2 may be at least one selected from the group consisting of methane, ethane, propane, butane, methanol, ethanol, propanol, propanediol, and butanediol. The compound represented by formula 3 may be at least one selected from the group consisting of ethylene, propylene, butylene, butadiene, and cyclopentene. The compound represented by formula 4 may be at least one selected from the group consisting of acetylene, benzene, toluene, xylene, ethylbenzene, naphthalene, anthracene, and dibutylhydroxytoluene (BHT).
[0190] The carbon source gas may further include at least one inert gas selected from hydrogen, nitrogen, helium, and argon. In addition, at least one gas selected from water vapor, carbon monoxide, and carbon dioxide may be added together with the carbon source gas.
[0191] When water vapor is added to the reaction, the silicon-silicon complex oxide-carbon composite material can have a higher electrical conductivity.
[0192] According to an embodiment of the present invention, when water vapor is added to the reaction, a carbon layer having high crystallinity is formed on the surface of the composite material, so that high conductivity can be achieved even if a small amount of carbon is coated. The content of water vapor is not particularly limited. For example, it may be 0.01 to 10 volume % based on 100 volume % of the total carbon source gas.
[0193] The carbon source gas may be, for example, methane, a gas mixture comprising methane and an inert gas, an oxygen-containing gas, or a gas mixture comprising methane and an oxygen-containing gas.
[0194] According to one embodiment, the carbon source gas may be a mixture of CH4 and CO2, or a mixture of CH4, CO2, and H2O.
[0195] The mixed gas of CH4 and CO2 may be provided in a molar ratio of about 1:0.20-0.50. Specifically, the mixed gas of CH4 and CO2 may have a molar ratio of about 1:0.25-0.45. More specifically, the mixed gas of CH4 and CO2 may have a molar ratio of about 1:0.30-0.40.
[0196] Furthermore, the mixed gas of CH4, CO2, and H2O may have a molar ratio of about 1:0.20-0.50:0.01-1.45, specifically, a molar ratio of about 1:0.25-0.45:0.10-1.35, particularly, a molar ratio of about 1:0.30-0.40:0.50-1.0.
[0197] According to another embodiment, the carbon source gas may be a mixture of CH4 and N2.
[0198] The mixed gas of CH4 and N2 may have a molar ratio of about 1:0.20-0.50, specifically about 1:0.25-0.45, and more specifically about 1:0.30-0.40.
[0199] Furthermore, according to one embodiment, the carbon source gas may be free of inert gases such as nitrogen.
[0200] The reaction can be carried out at 600°C to 1,200°C, specifically 700°C to 1,100°C, and more specifically 700°C to 1,000°C.
[0201] The pressure during the heat treatment can be selected in consideration of the heat treatment temperature, the composition of the mixed gas, the amount of carbon coating, etc. The pressure during the heat treatment can be controlled by adjusting the amount of the mixed gas introduced and discharged. For example, the pressure during the heat treatment can be 0.1 atmosphere or more, for example, 0.5 atmosphere or more, 1 atmosphere or more, 2 atmospheres or more, 3 atmospheres or more, or 5 atmospheres or more, but is not limited thereto.
[0202] The reaction time (or heat treatment time) can be appropriately adjusted depending on the heat treatment temperature, the pressure during heat treatment, the composition of the mixed gas, and the desired carbon coating amount. For example, the reaction time may be, but is not limited to, 10 minutes to 100 hours, specifically, 30 minutes to 90 hours, and more specifically, 50 minutes to 40 hours. Without being bound by any particular theory, the longer the reaction time, the thicker the carbon layer formed will be, and the better the electrical properties of the composite material will be.
[0203] In the method for preparing a silicon-silicon complex oxide-carbon composite material according to one embodiment of the present invention, a thin and uniform carbon layer containing at least one selected from graphene, reduced graphene oxide, carbon nanotubes and carbon nanofibers as a main component can be formed on the surface of the silicon-silicon complex oxide composite material by a gas-phase reaction of a carbon source gas even at a relatively low temperature. Furthermore, the carbon layer thus formed does not substantially undergo a peeling reaction.
[0204] According to the preparation method of the present invention, a raw material obtained by using silicon powder and silicon oxide powder is reacted with metallic magnesium to obtain a silicon-silicon complex oxide composite material (core) containing silicon, a silicon oxide compound, and magnesium silicate, and a carbon layer is formed on the surface of the silicon-silicon complex oxide composite material to obtain a composite material having a core-shell structure. In addition, the carbon layer does not substantially contain magnesium or its oxide component.
[0205] In addition, since a carbon layer is formed uniformly over the entire surface of the silicon-silicon oxide composite material by the gas phase reaction, a carbon film (carbon layer) with high crystallinity can be formed. Thus, when this composite material is used as a negative electrode active material, the conductivity of the negative electrode active material can be improved without changing the structure.
[0206] Also, the specific surface area of the composite material may decrease depending on the amount of carbon coating.
[0207] The structure of the graphene-containing material may be layered, nanosheet-like, or a mixture of multiple flakes.
[0208] If a carbon layer containing a graphene-containing material is uniformly formed on the entire surface of a silicon-silicon complex oxide-carbon composite material, the electrical conductivity of the silicon, silicon oxide compound, and magnesium silicate surfaces is increased, and the graphene-containing material, which is flexible against volume expansion, grows directly on the surfaces, so that volume expansion can be suppressed. In addition, the carbon layer coating reduces the possibility of silicon coming into direct contact with the electrolyte, thereby suppressing the formation of a solid electrolyte inter-compound layer.
[0209] In this manner, since the core of the silicon-silicon complex oxide-carbon composite material is fixed by the shell of the graphene-containing material, even if a binder is not used in the preparation of the negative electrode active material composition, structural collapse due to the volume expansion of silicon, the silicon oxide compound, and magnesium silicate can be suppressed, and by suppressing an increase in resistance, the composition can be advantageously used in the production of electrodes and lithium secondary batteries having excellent electrical conductivity and capacity characteristics.
[0210] In the method for preparing the composite material, the fifth step may include subjecting the composite material having a core-shell structure to at least one of a crushing and classification step to obtain a silicon-silicon complex oxide-carbon composite material (composite material C).
[0211] According to one embodiment of the present invention, the composite having a core-shell structure is subjected to grinding and / or classification to achieve the desired particle size distribution in the present invention.
[0212] In the fifth step, the composite material having a core-shell structure may be classified. Alternatively, the composite material having a core-shell structure may be pulverized. Alternatively, the composite material having a core-shell structure may be pulverized and classified. Specifically, the composite material having a core-shell structure may be classified and, if necessary, pulverized.
[0213] The pulverization and classification can be carried out in the same manner as in the pulverization and classification used in the third step.
[0214] Furthermore, the silicon-silicon complex oxide-carbon composite material may be pulverized and / or classified to have an average particle diameter of 0.5 μm to 10 μm, specifically 3.0 μm to 8.0 μm, more specifically 3.0 μm to 7.0 μm.
[0215] In the present invention, the span value of Equation 1 can be controlled in the range of 0.6 to 1.5 by the grinding and / or classification process. Also, the D50, D10, and D90 of the silicon-silicon complex oxide-carbon composite material can be controlled in the optimum range. Furthermore, it is preferable to reduce fine particles and coarse particles using a classifier or sieve after grinding.
[0216] negative electrode active material An embodiment of the negative electrode active material may include the silicon-silicon complex oxide-carbon composite material. Specifically, the negative electrode active material includes a silicon-silicon complex oxide-carbon composite material having a core-shell structure, the core includes silicon, a silicon oxide compound, and magnesium silicate, the shell includes a carbon layer, and the span value of the above equation 1 of the composite material is 0.6 to 1.5 when the particle sizes at which the cumulative volume concentration (%) in the particle size distribution is 10%, 50%, and 90% are D10, D50, and D90, respectively.
[0217] In addition, the anode active material may further include a carbon-based anode material, specifically, a graphite-based anode material.
[0218] The negative electrode active material can be a mixture of a silicon-silicon complex oxide-carbon composite material and a carbon-based negative electrode material, for example, a graphite-based negative electrode material. In such a case, the electrical resistance of the negative electrode active material can be reduced while at the same time alleviating the expansion stress caused by charging. The carbon-based negative electrode material can include at least one selected from the group consisting of natural graphite, synthetic graphite, soft carbon, hard carbon, mesocarbon, carbon fiber, carbon nanotube, pyrolytic carbon, coke, glass-carbon fiber, sintered organic polymer compound, and carbon black.
[0219] The silicon-silicon complex oxide-carbon composite material can be used in an amount of 5% to 90% by weight, specifically 20% to 60% by weight, and more specifically 30% to 50% by weight, based on the total weight of the negative electrode active material.
[0220] Further, the carbon-based negative electrode material can be used in an amount of 30% to 90% by weight, specifically 40% to 80% by weight, and more specifically 50% to 80% by weight, based on the total weight of the negative electrode active material.
[0221] secondary battery According to one embodiment of the present invention, the present invention can provide a negative electrode including a negative electrode active material, and a secondary battery including the same.
[0222] The secondary battery may include a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and a non-aqueous electrolyte solution having a lithium salt dissolved therein. The negative electrode may include a negative electrode active material including a silicon-silicon complex oxide-carbon composite material.
[0223] The negative electrode may be composed of only the negative electrode mixture, or may be composed of a negative electrode current collector and a negative electrode mixture layer (negative electrode active material layer) supported thereon. Similarly, the positive electrode may be composed of only the positive electrode mixture, or may be composed of a positive electrode current collector and a positive electrode mixture layer (positive electrode active material layer) supported thereon. In addition, the negative electrode mixture and the positive electrode mixture may further include a conductive material and a binder.
[0224] Materials known in the art can be used as the materials constituting the negative electrode current collector and the positive electrode current collector. Materials known in the art can be used as the binder and conductor material added to the negative electrode and positive electrode.
[0225] When the negative electrode is composed of a current collector and an active material layer supported thereon, the negative electrode can be prepared by applying a negative electrode active material composition containing a silicon-silicon complex oxide-carbon composite material having a core-shell structure to the surface of the current collector and drying it.
[0226] Further, the secondary battery includes a non-aqueous liquid electrolyte, and the non-aqueous liquid electrolyte may include a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent. As the non-aqueous solvent, a solvent commonly used in the art may be used. Specifically, an aprotic organic solvent may be used. Examples of the aprotic organic solvent include cyclic carbonates such as ethylene carbonate, propylene carbonate, and butylene carbonate, cyclic carboxylic acid esters such as furanone, chain carbonates such as diethyl carbonate, ethyl methyl carbonate, and dimethyl carbonate, chain ethers such as 1,2-methoxyethane, 1,2-ethoxyethane, and ethoxymethoxyethane, and cyclic ethers such as tetrahydrofuran and 2-methyltetrahydrofuran. They may be used alone or in combination of two or more.
[0227] The secondary battery may include a non-aqueous secondary battery.
[0228] The negative electrode active material and secondary battery using this silicon-silicon complex oxide-carbon composite material can improve the capacity, initial charge-discharge efficiency, and capacity retention rate. EXAMPLES
[0229] The present invention will be described in detail below with reference to examples. The following examples are merely examples of the present invention, and the scope of the present invention is not limited thereto.
[0230] <Example 1> Preparation of silicon-silicon complex oxide-carbon composite materials Step 1: 11 kg of silicon powder having an average particle diameter of 20 μm and 15 kg of silicon dioxide powder having an average particle diameter of 20 nm were added to 60 kg of water, and the mixture was stirred in a PL mixer for 12 hours to uniformly mix them, and then dried at 250° C. for 20 hours under a nitrogen atmosphere. The resultant was then dried again at 600° C. for 12 hours to form a raw material powder mixture (raw material).
[0231] Step 2: The raw powder mixture and 3 kg of metallic magnesium were placed in crucible-A and crucible-B in a vacuum reactor, respectively. After the pressure was lowered to 0.01 Torr, crucible-A was heated to 1400°C and crucible-B was heated to 700°C, and the mixture was reacted for 5 hours to adhere to the adhesion substrate in the reactor. The adhesion substrate was quenched to room temperature by water cooling to obtain the silicon-silicon oxide composite material (composite material A1) that was the core.
[0232] Step 3: The silicon-silicon complex oxide composite material (composite material A1) was pulverized once in a jet mill (manufactured by Netz Co., Ltd.) under conditions of an air pressure of 7.5 bar, a classifier rotation speed of 1,300 rpm, and a feed speed of 216 rpm, and then collected in a cyclone. The collected pulverized material gave a silicon-silicon complex oxide composite material powder (composite material B1) with a D10 of 3.2 μm, a D50 of 6.0 μm, and a D90 of 9.5 μm.
[0233] Step 4: The silicon-silicon oxide composite powder (composite material B1) was placed in an electric furnace. The pressure was reduced to 0.2 Torr using a rotary vacuum pump. Then, argon gas was introduced at a flow rate of 0.3 liters / min to reach normal pressure. Once normal pressure was reached, the temperature of the electric furnace was raised to 1,000°C at a rate of 200°C / hr. Once 1,000°C was reached, methane gas was injected into the electric furnace at a flow rate of 0.3 liters / min to perform a carbon coating process for 10 hours. After stopping the supply of methane gas, the electric furnace was cooled to room temperature to obtain a composite material having a core-shell structure with an average particle diameter of 6.7 μm.
[0234] Step 5: The core-shell structured composite was passed through a vibrating filter equipped with a 420 mesh sieve to obtain the final silicon-silicon complex oxide-carbon composite (Composite C1) with controlled particle size distribution of D10 of 3.85 μm, D50 of 5.96 μm, and D90 of 9.08 μm.
[0235] Secondary battery manufacturing A negative electrode and battery (coin cell) were fabricated containing a silicon-silicon complex oxide-carbon composite material (composite material C1) with controlled particle size distribution as the negative electrode active material.
[0236] This negative electrode active material, Super-P as a conductive material, and polyacrylic acid were mixed with water in a weight ratio of 80:10:10 to prepare a negative electrode active material composition with a solid content of 45%.
[0237] The negative electrode active material composition was applied to a copper foil having a thickness of 18 μm and dried to prepare an electrode having a thickness of 70 μm. The copper foil covered with the electrode was punched out into a circle having a diameter of 14 mm to prepare a negative electrode plate for a coin cell.
[0238] On the other hand, a 0.3 mm thick metallic lithium foil was used as the positive electrode plate.
[0239] A 25 μm thick porous polyethylene sheet was used as the separator. A liquid electrolyte was used in which LiPF6 was dissolved at a concentration of 1 M in a mixed solvent of ethylene carbonate (EC) and diethylene carbonate (DEC) in a volume ratio of 1:1. Using the above components, a coin cell (battery) with a thickness of 3.2 mm and a diameter of 20 mm was manufactured.
[0240] <Example 2> The composite material C1 from step 5 of Example 1 was mixed with an air classifier (TC type, manufactured by Nissin Co., Ltd.) at a blower volume of 4.5 m 3 A silicon-silicon complex oxide-carbon composite material and a secondary battery were produced in the same manner as in Example 1, except that the silicon-silicon complex oxide-carbon composite material was classified once under conditions of a rotor speed of 3,000 rpm, a rotor speed of 3,000 rpm, and recovery in a cyclone to prepare a silicon-silicon complex oxide-carbon composite material (composite material C2) having the particle size distribution shown in Table 1.
[0241] <Example 3> The composite material C1 from step 5 of Example 1 was mixed with an air classifier (TC type, manufactured by Nissin Co., Ltd.) at a blower volume of 4.7 m 3 A silicon-silicon complex oxide-carbon composite material and a secondary battery were produced in the same manner as in Example 1, except that the silicon-silicon complex oxide-carbon composite material was classified once under conditions of a rotor speed of 6,500 rpm, a rotor speed of 6,500 rpm, and recovery in a cyclone to prepare a silicon-silicon complex oxide-carbon composite material (composite material C3) having the particle size distribution shown in Table 1.
[0242] <Example 4> The composite material C1 from step 5 of Example 1 was mixed with an air classifier (TC type, manufactured by Nissin Co., Ltd.) at a blower volume of 4.2 m 3 A silicon-silicon complex oxide-carbon composite material and a secondary battery were produced in the same manner as in Example 1, except that the silicon-silicon complex oxide-carbon composite material was classified once under conditions of a rotor speed of 4,000 rpm at a flow rate of 1000 μm / min and a rotor speed of 4,000 rpm, and recovered using a cyclone to prepare a silicon-silicon complex oxide-carbon composite material (composite material C4) having the particle size distribution shown in Table 1.
[0243] <Example 5> The composite material C1 from step 5 of Example 1 was mixed with an air classifier (TC type, manufactured by Nissin Co., Ltd.) at a blower volume of 6.5 m 3 A silicon-silicon complex oxide-carbon composite material and a secondary battery were produced in the same manner as in Example 1, except that the silicon-silicon complex oxide-carbon composite material (composite material C5) having the particle size distribution shown in Table 1 was prepared by classifying the silicon-silicon complex oxide-carbon composite material once under conditions of a rotor speed of 6,500 rpm and a rotor speed of 6,500 rpm.
[0244] <Example 6> A silicon-silicon complex oxide-carbon composite material (composite material C6) having the particle size distribution shown in Table 1 and a secondary battery were produced in the same manner as in Example 1, except that the pulverization in step 3 in Example 1 was carried out twice to prepare a silicon-silicon complex oxide composite material powder (composite material B2) having an average particle diameter of about 4.9 μm.
[0245] <Example 7> A silicon-silicon complex oxide-carbon composite material (composite material C7) having the particle size distribution shown in Table 1 and a secondary battery were produced in the same manner as in Example 1, except that the grinding in step 3 of Example 1 was carried out three times to prepare a silicon-silicon complex oxide composite material powder (composite material B3) having an average particle diameter of about 1.9 μm.
[0246] <Example 8> A silicon-silicon complex oxide composite material (composite material A1) from step 3 of Example 1 was pulverized once in a jet mill (small, manufactured by Daega) under conditions of an air pressure of 8.0 bar, a classifier rotation speed of 2,200 rpm, and a feeder speed of 600 rpm, and then collected in a cyclone to prepare a silicon-silicon complex oxide composite material powder (composite material B4) having an average particle diameter of 6.3 μm. A silicon-silicon complex oxide-carbon composite material (composite material C8) and a secondary battery having the particle size distribution shown in Table 1 were produced in the same manner as in Example 1.
[0247] <Example 9> Instead of the raw material powder mixture in step 1 of Example 1, SiO xA silicon-silicon complex oxide-carbon composite material (composite material C9) and a secondary battery having the particle size distribution shown in Table 1 were produced in the same manner as in Example 1, except that the (x=1.08) compound was used.
[0248] <Example 10> A silicon-silicon complex oxide-carbon composite material (composite material C10) and a secondary battery having the particle size distribution shown in Table 1 were produced in the same manner as in Example 1, except that the carbon coating treatment in step 4 of Example 1 was carried out in an electric furnace with stirring at 0.1 rpm for 10 hours while flowing methane at 0.3 L / min.
[0249] <Comparative Example 1> A silicon-silicon complex oxide-carbon composite material and a secondary battery having the particle size distribution shown in Table 1 were produced in the same manner as in Example 1, except that the silicon-silicon complex oxide composite material (composite material A1) from step 3 of Example 1 was pulverized in a jet mill (small, manufactured by Daega) at an air pressure of 0.58 MPa to prepare a silicon-silicon complex oxide composite material (composite material B5) having an average particle diameter of 12.8 μm as the pulverized product.
[0250] <Comparative Example 2> In step 2 of Example 1, no metallic magnesium was used, and the SiO x A silicon-silicon complex oxide-carbon composite material and a secondary battery having the particle size distribution shown in Table 1 were produced in the same manner as in Example 1, except that in step 3, (x=1.02) was pulverized in a ball mill to obtain a composite powder having an average particle size of 3.7 μm.
[0251] <Comparative Example 3> In step 3 of Example 1, pulverization using a jet mill was not performed, but an air flow classifier was used with an air volume of 2.5 Nm 3 A silicon-silicon oxide composite material (composite material A1) was classified at a rotor speed of 10,000 rpm and a rotor rotation speed of 10,000 rpm. A composite material and a secondary battery having the particle size distribution shown in Table 1 were produced in the same manner as in Comparative Example 1, except that steps 4 and 5 were not performed.
[0252] Test Example Test Example 1: Measurement of particle diameter of the final composite material 0.2 g of the final composite particles prepared in the examples and comparative examples were dispersed in 10 mL of ethanol and subjected to ultrasonic treatment for 3 minutes. After that, the particle size was measured using a Microtrac S3500 device. In the particle size distribution measurement using the laser light diffraction method, the analytical values D10, D50, and D90 were measured as the particle diameter when the cumulative volume concentration (%) was 10% (D10), the particle diameter when the cumulative volume concentration (%) was 50% (D50), and the particle diameter when the cumulative volume concentration (%) was 90% (D90), respectively.
[0253] 1 is a graph showing the results of measuring the particle size distribution of the silicon-silicon complex oxide-carbon composite material of Example 1. It shows the cumulative volume concentration (%) and the volume concentration (%) with respect to the particle size of the silicon-silicon complex oxide-carbon composite material.
[0254] As shown in FIG. 1, in Example 1, D10 was 3.85 μm, D50 was 5.96 μm, and D90 was 9.08 μm.
[0255] Test Example 2: Measurement of the specific surface area of the final composite material The composite materials prepared in the examples and comparative examples were degassed for 2 hours at 350° C. Their specific surface areas were measured by the BET single-point method using a mixture of nitrogen and helium gas (N2: 30% by volume, He: 70% by volume) with a Mountec Macsorb HM (1210 model).
[0256] Test Example 3: Measurement of the electrical conductivity of the final composite material Using a hard mask on the top and bottom of the composite materials prepared in the examples and comparative examples, gold (Au) was deposited to a thickness of 100 nm in an argon (Ar) atmosphere at 100 W to obtain cells. The ionic conductivity at 25°C was measured from the response obtained by applying an alternating current at two blocking electrodes using an impedance analyzer (Zahner, IM6).
[0257] Test Example 4: Analysis of the content and specific gravity of the component elements of the final composite material The composite materials prepared in the examples and comparative examples were analyzed for the contents of the component elements magnesium (Mg), oxygen (O) and carbon (C).
[0258] The magnesium (Mg) content was analyzed by inductively coupled plasma (ICP) emission spectroscopy, while the oxygen (O) and carbon (C) contents were measured by an elemental analyzer.
[0259] 0.4 g of the prepared composite material was placed in a 10 ml container, and the specific gravity (particle density) was measured using Accupyc II manufactured by Micromeritics. Test Example 5: Measurement of capacity, initial efficiency, and capacity retention rate of secondary batteries
[0260] The coin cells (secondary batteries) prepared in the examples and comparative examples were charged at a constant current of 0.1 C until the voltage reached 0.005 V, and discharged at a constant current of 0.1 C until the voltage reached 2.0 V, and the charge capacity (mAh / g), discharge capacity (mAh / g), and initial efficiency (%) were measured according to the following equation 2. The results are shown in Table 1 below.
[0261] [Equation 2] Initial efficiency (%) = discharge capacity / charge capacity x 100
[0262] In addition, the coin cells prepared in the examples and comparative examples were each charged and discharged once in the same manner as above, and from the second cycle onwards, they were charged at a constant current of 0.5 C until the voltage reached 0.005 V, and discharged at a constant current of 0.5 C until the voltage reached 2.0 V, and the cycle characteristics (capacity retention rate at 100 cycles, %) were measured according to the following equation 3. The results are shown in Table 1 below.
[0263] [Equation 3] Capacity retention rate at 100 cycles (%) = 101st discharge capacity / 2nd discharge capacity x 100
[0264] [Table 1]
[0265] As can be seen from Table 1, the secondary batteries fabricated using the silicon-silicon complex oxide-carbon composite materials with controlled particle size distribution of Examples 1 to 10 of the present invention had significantly improved initial efficiency, initial capacity, and cycle characteristics (life characteristics) compared to Comparative Examples 1 to 3.
[0266] Specifically, in all the composite materials of Examples 1 to 10, the span value of Equation 1 satisfied 0.6 to 1.5. The secondary batteries manufactured using these materials had excellent initial capacities of 1,400mAh / g to 1,424mAh / g overall, and initial efficiencies of 78.5% or more. In particular, the capacity retention rate at 100 cycles was mostly 90% or more.
[0267] On the other hand, the composite materials of Comparative Examples 1 to 3 all had span values in Equation 1 that exceeded 1.5, falling outside the range of the desired span value in the present invention. Specifically, the secondary battery of Comparative Example 1, which used a composite material with a span value exceeding 2, had an extremely low initial capacity of 1,358 mAh / g. The secondary battery of Comparative Example 2, which used a composite material that did not contain magnesium and had a span value of 1.59, had a significantly low initial efficiency of 75.4%. The secondary battery of Comparative Example 3, which did not contain a carbon layer and had a span value of 1.68, had significantly reduced life characteristics, initial capacity, and initial efficiency compared to the secondary batteries of the Examples.
Claims
1. A silicon-silicon complex oxide-carbon composite material having a core-shell structure, wherein the core comprises silicon, a silicon oxide compound, and magnesium silicate, and the shell comprises a carbon layer, and the span value of the following equation 1 of the composite material is 0.6 to 1.5 when D10, D50, and D90 are particle sizes at which cumulative volume concentrations (%) in a particle size distribution are 10%, 50%, and 90%, respectively. [Equation 1] Span = (D90 - D10) / D50
2. 2. The silicon-silicon complex oxide-carbon composite material of claim 1, wherein said composite material has a D50 of 0.5 μm to 10.0 μm.
3. 2. The silicon-silicon complex oxide-carbon composite material of claim 1, wherein said composite material has a D10 of 0.7 μm to 4.0 μm, and a D90 of 3.0 μm to 12.0 μm.
4. 2. The silicon-silicon complex oxide-carbon composite material of claim 1, wherein said composite material has a D90 / D10 of 1.0 to 5.
0.
5. 2. The silicon-silicon complex oxide-carbon composite material of claim 1, wherein said silicon is in amorphous form, crystalline form having a crystallite size of 2 nm to 20 nm, or a mixture thereof.
6. 2. The silicon-silicon complex oxide-carbon composite material of claim 1, wherein the content of silicon (Si) in the core is 30% to 80% by weight based on the total weight of the silicon-silicon complex oxide-carbon composite material.
7. 2. The silicon-silicon complex oxide-carbon composite material of claim 1, wherein the ratio of the number of oxygen atoms to the number of silicon atoms present in said silicon-silicon complex oxide-carbon composite material (O / Si) is 0.45 to 1.
2.
8. 2. The silicon-silicon complex oxide-carbon composite material of claim 1, wherein said silicon oxide compound is SiOx (0.5≦x≦1.5).
9. 2. The silicon-silicon complex oxide-carbon composite material of claim 1, wherein the content of magnesium (Mg) in the silicon-silicon complex oxide-carbon composite material is 2% by weight to 15% by weight based on the total weight of the silicon-silicon complex oxide-carbon composite material.
10. In the X-ray diffraction analysis of the magnesium silicate, Mg appears in the range of 2θ = 22.3 ° to 23.3 °. 2 SiO 4 The X-ray diffraction peak intensity (IF) corresponding to the crystal appears in the range of 2θ = 30.5° to 31.5°. 3 2. The silicon-silicon complex oxide-carbon composite material of claim 1, wherein the ratio (IF / IE) of the intensity of the X-ray diffraction peak corresponding to the crystal to the intensity (IE) is greater than 0 and less than or equal to 1.
11. 2. The silicon-silicon complex oxide-carbon composite material of claim 1, wherein the carbon layer comprises at least one selected from the group consisting of graphene, reduced graphene oxide, carbon nanotubes, and carbon nanofibers.
12. The silicon-silicon complex oxide-carbon composite material of claim 11, wherein said carbon layer further comprises graphite.
13. 2. The silicon-silicon complex oxide-carbon composite material of claim 1, wherein the content of carbon (C) in the carbon layer is 2% by weight to 30% by weight based on the total weight of the silicon-silicon complex oxide-carbon composite material.
14. 2. The silicon-silicon complex oxide-carbon composite material of claim 1, wherein said carbon layer has a thickness of from 1 nm to 300 nm.
15. The silicon-silicon complex oxide-carbon composite material has a density of 1.7 g / cm 3 ~2.6g / cm 3 Specific gravity, and 3m 2 / g to 30m 2 2. The silicon-silicon complex oxide-carbon composite material of claim 1, having a specific surface area (Brunauer-Emmett-Teller method; BET) of 1.0 x 100 / g.
16. Silicon powder and silicon oxide (SiO x , 0.5≦x≦2) a first step of preparing a raw material obtained using the powder; A second step of heating and evaporating the raw material and metallic magnesium at different temperatures, then depositing them and cooling them to obtain a silicon-silicon oxide composite material as a core; A third step of crushing and classifying the silicon-silicon composite oxide composite material to obtain a silicon-silicon composite oxide composite material powder having an average particle diameter of 0.5 μm to 10 μm; A fourth step of forming a carbon layer on the surface of the silicon-silicon composite oxide powder by chemical pyrolysis deposition to obtain a composite material having a core-shell structure; and A fifth step of subjecting the composite material having a core-shell structure to at least one step of pulverization and classification to obtain a silicon-silicon complex oxide-carbon composite material.
2. A method for preparing the silicon-silicon complex oxide-carbon composite material of claim 1, comprising:
17. The method for preparing a silicon-silicon complex oxide-carbon composite material according to claim 16, wherein the raw material is a mixture obtained by mixing silicon powder and silicon oxide powder, or a compound obtained by heating the mixture and cooling and condensing the gas generated thereby, or a blend of the mixture and the compound.
18. The method for preparing the silicon-silicon complex oxide-carbon composite material according to claim 17, wherein in the blend of the mixture and the compound, the compound is further added in an amount of 20 wt% to less than 100 wt% based on the total weight of the blend.
19. The method for preparing a silicon-silicon complex oxide-carbon composite material according to claim 17, wherein the silicon powder has an average particle diameter of 5 μm to 50 μm, and the silicon oxide powder has an average particle diameter of 5 nm to 50 nm.
20. 17. The method for preparing a silicon-silicon complex oxide-carbon composite material according to claim 16, wherein the raw material has a molar ratio of oxygen element per 1 mole of silicon element of 0.8 to 1.
2.
21. The method for preparing a silicon-silicon complex oxide-carbon composite material according to claim 16, wherein the heating and evaporation of the raw material in the second step is carried out at 900°C to 1800°C under a pressure of 0.0001 Torr to 2 Torr, and the heating and evaporation of the metallic magnesium in the second step is carried out at 500°C to 1100°C under a pressure of 0.0001 Torr to 2 Torr.
22. The method for preparing a silicon-silicon complex oxide-carbon composite material according to claim 16, wherein the formation of the carbon layer in the fourth step is carried out by injecting at least one compound selected from the compounds represented by the following formulas 2 to 4 and carrying out a reaction in a gaseous state at 600° C. to 1200° C. 【Chemistry 1】
23. 17. The method for preparing a silicon-silicon complex oxide-carbon composite material according to claim 16, wherein in the third step, the pulverization is carried out using at least one selected from the group consisting of a jet mill, a ball mill, a stirring media mill, a roll mill, a hammer mill, a pin mill, a disk mill, a colloid mill, and an atomizer mill, and the classification is carried out using at least one selected from dry classification, wet classification, and sieve classification.
24. 13. A negative electrode active material comprising the silicon-silicon complex oxide-carbon composite material of claim 1.
25. 25. The anode active material of claim 24, wherein the anode active material further comprises a carbon-based anode material.
26. 25. The negative electrode active material of claim 24, wherein the silicon-silicon complex oxide-carbon composite material is used in an amount of 5% to 90% by weight based on the total weight of the negative electrode active material.
27. A lithium secondary battery comprising the negative electrode active material of claim 24.
Citation Information
Patent Citations
Liquid crystal display unit
JP1979006799A
Non-aqueous electrolyte secondary battery
JP2002042806A
Cathode material for nonaqueous electrolytic secondary battery and method of manufacturing the same, and lithium ion secondary battery
JP2012033317A
Negative electrode active material for secondary battery, lithium secondary battery comprising the same, and method for manufacturing negative electrode for lithium secondary battery comprising the same
JP2013041826A
Compact nonaqueous electrolyte secondary battery and manufacturing method therefor
JP2013101770A